Design and Implementation of a Captive Portal Login System for Improved Network Security and User Access Management - Lisdianto Dwi Kesumahadi; Nuril Anwar; Feby Charlos; Bagus Setya (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
This study addresses network security issues and the suboptimal access time recording mechanism at the Informatics S1 Research Laboratory of Universitas Ahmad Dahlan. The research aims to design a hotspot system based on a Captive Portal, integrated with the existing MikroTik infrastructure, to enhance both security and efficiency. The study follows the Software Development Life Cycle (SDLC) methodology, encompassing the stages of requirements analysis, system design, implementation, testing, as well as operation and maintenance. Additionally, a Vulnerability Assessment is conducted to identify and address potential security weaknesses. The main objectives of this research include improving network security by preventing unauthorized access and data interception, as well as automating and accurately recording network usage duration for each user. The expected contribution of this work is the creation of a centralized authentication system that will optimize laboratory management and improve user experience. Preliminary results indicate a significant increase in network security and an efficient time-tracking mechanism, contributing to a 30% improvement in the lab's operational efficiency.